Cinematography Aesthetic Analysis of the Controversial Documentary Film “Ice Cold: Murder, Coffee, and Jessica Wongso” - Kristina, Ni Putu Ayu Cempaka Riska Intan (Institut Seni Indonesia Bali, 2025)
Documentary film is a medium used to present reality through visuals recorded based on existing facts. In its presentation, this film can include human thoughts, referring to documentary film theories that depict subjects in the form of real people, events or situations. This study aims to analyze the cinematographic aesthetics of the documentary film entitled